Naringin Relieves Diabetic Cardiac Autonomic Neuropathy Mediated by P2Y14 Receptor in Superior Cervical Ganglion - Tang, Gan; Pi, Lingzhi; Guo, Hongmin; Hu, Zihui; Zhou, Congfa; Hu, Qixing; Peng, Hao; Xiao, Zehao; Zhang, Zhihua; Wang, Miaomiao; Peng, Taotao; Huang, Jiaqi; et al. (Frontiers in Pharmacology, 2022)
Diabetes mellitus (DM), an emerging chronic epidemic, contributes to mortality and morbidity around the world. Diabetic cardiac autonomic neuropathy (DCAN) is one of the most common complications associated with DM. Previous studies have shown that satellite glial cells (SGCs) in the superior cervical ganglia (SCG) play an indispensable role in DCAN progression. In addition, it has been shown that purinergic neurotransmitters, as well as metabotropic GPCRs, are involved in the pathophysiological process of DCAN. Furthermore, one traditional Chinese medicine, naringin may potently alleviate the effects of DCAN. Ferroptosis may be involved in DCAN progression. However, the role of naringin in DCAN as well as its detailed mechanism requires further investigation. In this research, we attempted to identify the effect and relevant mechanism of naringin in DCAN mitigation. We observed that compared with those of normal subjects, there were significantly elevated expression levels of P2Y14 and IL-1β in diabetic rats, both of which were remarkably diminished by treatment with either P2Y14 shRNA or naringin. In addition, abnormalities in blood pressure (BP), heart rate (HR), heart rate variability (HRV), sympathetic nerve discharge (SND), and cardiac structure in the diabetic model can also be partially returned to normal through the use of those treatments. Furthermore, a reduced expression of NRF2 and GPX4, as well as an elevated level of ROS, were detected in diabetic cases, which can also be improved with those treatments. Our results showed that naringin can effectively relieve DCAN mediated by the P2Y14 receptor of SGCs in the SCG. Moreover, the NRF2/GPX4 pathway involved in ferroptosis may become one of the principal mechanisms participating in DCAN progression, which can be modulated by P2Y14-targeted naringin and thus relieve DCAN. Hopefully, our research can supply one novel therapeutic target and provide a brilliant perspective for the treatment of DCAN.